Development and validation of technological pedagogical content knowledge (TPACK) test instruments for prospective chemistry teachers - Rifa, Hasna Athaya; Nahadi, Nahadi; Sjaeful, Sjaeful (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aimed to develop a digital-based test instrument to assess the technological, pedagogical, and content knowledge of pre-service chemistry teachers. The instrument was designed based on the TPACK framework, which consists of seven interrelated components: Content Knowledge (CK), Pedagogical Knowledge (PK), Technological Knowledge (TK), Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK), and the integrated TPACK domain. A total of 20 indicators were constructed, and corresponding items were developed in digital format. Content validation involved three chemistry education experts who evaluated each item based on three aspects: alignment with the indicator, clarity of the correct answer, and appropriateness of the scoring rubric. Using a binary scale (“Yes” = relevant, “No” = not relevant), data were analyzed through the Content Validity Index (CVI). The findings show that 18 out of 20 items achieved acceptable I-CVI values (≥ 0.78), and the overall S-CVI/Ave score was 0.95, indicating excellent content validity. This suggests that the developed instrument is valid for assessing TPACK and can support future efforts in preparing technology-integrated chemistry teaching.